Concussion and Age Effects on the Stability of the Mismatch Negativity Brain Response - Lu, Gwenyth (My University, 2024)
There is a large literature describing the effects of concussion on cognitive processes including attention and memory. Electroencephalography (EEG) is a neuroimaging tool that records brain electrical activity from the scalp using electrodes and has a distinguished history in medicine examining many neurological conditions such as epilepsy and sleep abnormalities. Derived from EEG, event-related potentials (ERPs) are neurophysiological responses that are differentially sensitive to specific cognitive processes. A much-investigated ERP component called the mismatch negativity (MMN) has been employed usefully in concussion research to assess changes in automatic attention. In the context of concussion, the stability of the MMN in a single test session and test-retest changes in the response have received little attention. The present thesis examined the internal consistency/reliability of the MMN component in four groups: concussed adolescents, retired Canadian Football League (rCFL) players, and respective groups of age-matched healthy controls. The number of trials necessary for the MMN to be elicited with a high degree of internal consistency was assessed for both amplitude and area under the curve (AUC) values. Cronbach’s alpha was used as a measure of internal MMN consistency and changes in responses to deviant stimuli were employed in the oddball paradigm separately for each group. Data from each group revealed a significant effect of the number of trials on the reliability of the MMN. The concussed adolescents showed stronger MMN stability compared to the rCFL athletes in comparison to each groups’ respective controls. The adolescent control group revealed lower response stability than the control group with the older adults. A stable MMN (α ≥ 0.80) was achieved with 130 trials across all groups and stimuli. The findings demonstrate that the MMN is abnormal in rCFL athletes coping with post-concussion syndrome (PCS) whereas adolescents seem to have a reduced vulnerability to the symptoms of concussion.